Pengembangan Media Pembelajaran Interaktif Untuk Mata Kuliah Sumber Energi Baru Terbarukan Di Program Studi D-IV Teknologi Rekayasa Pembangkit Energi: Development of Interactive Learning Media for New Renewable Energy Sources Courses in the Energy Generation Engineering Technology D-IV Study - Rifat Rifat; Ivan Maududy; Rully Rezki Saputra (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2023)
The world of education cannot be separated from developments in technology, information and communication. The very rapid development of technology today has provided many benefits in helping human activities in various aspects of life, one of which is the world of education. The main point in educational activities is a process called learning and communicating. Apart from communication, interactive learning media is needed which aims to ensure that the learning process can run optimally. There are several alternative media choices that can be used to convey learning material in the world of education, one of these media is interactive learning media based on Adobe Flash or PowerPoint. This research shows that based on material experts, aspects of material content, material presentation, language aspects and usefulness aspects obtained a total score of 48.00 with a very decent category. The results of the media expert's assessment based on media display aspects, programming aspects and usability aspects obtained a total score of 43.00 with a very decent category. Assessment by students in small group trials based on media display aspects, material presentation aspects, programming aspects, and usefulness aspects obtained a total score of 57.00 with a very decent category. Assessment by students in large group trials based on media display aspects, material presentation aspects, programming aspects and usefulness aspects obtained a total score of 59.16 in the very decent category. The overall assessment results show that the media is very suitable for use as an interactive learning medium in the New Renewable Energy Sources Course in the Banjarmasin State Polytechnic Energy Generation Engineering Technology Study Program.